2016
DOI: 10.3847/0004-637x/818/1/39
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Hydra I Is a Tidally Disrupting Milky Way Dwarf Galaxy

Abstract: The Eastern Banded Structure (EBS) and Hydra I halo overdensity are very nearby (d ∼ 10 kpc) objects discovered in SDSS data. Previous studies of the region have shown that EBS and Hydra I are spatially coincident, cold structures at the same distance, suggesting that Hydra I may be the EBS's progenitor. We combine new wide-field DECam imaging and MMT/Hectochelle spectroscopic observations of Hydra I with SDSS archival spectroscopic observations to quantify Hydra I's presentday chemodynamical properties, and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…3. Luminosity-metallicity relation for dwarf galaxies in the Cen A group (crosses, triangles, squares; Rejkuba et al 2006;Crnojević et al 2010Crnojević et al , 2011bCrnojević et al , 2019Müller et al 2019b) and Local Group (black dots, McConnachie 2012, from the updated online catalog, and are compiled from different sources, for example from Bellazzini et al 2004;Martin et al 2009;Correnti et al 2009;Kirby et al 2013;Torrealba et al 2016;Hargis et al 2016;Muñoz et al 2018). The dwarfs from this work are indicated as red dots.…”
Section: Properties Of the Stellar Populationsmentioning
confidence: 99%
“…3. Luminosity-metallicity relation for dwarf galaxies in the Cen A group (crosses, triangles, squares; Rejkuba et al 2006;Crnojević et al 2010Crnojević et al , 2011bCrnojević et al , 2019Müller et al 2019b) and Local Group (black dots, McConnachie 2012, from the updated online catalog, and are compiled from different sources, for example from Bellazzini et al 2004;Martin et al 2009;Correnti et al 2009;Kirby et al 2013;Torrealba et al 2016;Hargis et al 2016;Muñoz et al 2018). The dwarfs from this work are indicated as red dots.…”
Section: Properties Of the Stellar Populationsmentioning
confidence: 99%
“…Crater I; Kirby et al 2015;Voggel et al 2016). We also do not consider overdensities that are thought to be tidally disrupting dwarf galaxies: Boötes III (Carlin et al 2009;Carlin & Sand 2018), Canis Major (Martin et al 2004), and Hydra I (Hargis et al 2016). Furthermore, we restrict our analysis to satellites which have published line-of-sight velocities in order to have full 6-D kinematic information.…”
Section: Proper Motionsmentioning
confidence: 99%
“…Indeed, Grillmair (2011) suggested that a relatively high surface density, double-lobed feature found along the stream -called Hydra I -could be the dwarf galaxy or globular cluster progenitor of the stream. However, while the shallow SDSS imaging assumed an old, metal-poor stellar population, deeper imaging and spectroscopy of Hydra I by Hargis et al (2016) , which is only slightly more metal-poor than the thick disc ([Fe/H] ∼ −0.7, e.g Gilmore & Wyse 1985). It is clear that a kinematic exploration of the anti-centre region is desperately needed to dissect these complex structures.…”
Section: Introductionmentioning
confidence: 99%